Analysis of causes of maternal mortality in Sukabumi West Java - Saputri, Nurwinda; Suwarsa, Oki; Susiarno, Hadi (Universitas Aisyah Pringsewu, 2020)
There was 54 maternal mortality in Sukabumi District in 2015. The government has made various efforts to reduce maternal mortality cases, but the results have not been optimal. Identification of appropriate causes of maternal mortality provides valuable input in the prevention of future mortality. The objective of this study is to analyze the factors that play a role in maternal mortality and explore how these factors cause maternal mortality. Design research uses explanatory sequential designated mixed methods which are carried out in stages. The first step was to conduct a documentation study of 54 cases of maternal mortality at Verbal Maternal Autopsy and a statistical calculation was made using a cross-sectional approach. The results of the document study were then carried out qualitatively by in-depth interview methods. The results showed that there were groupings of maternal mortality in the district of Sukabumi namely in the District of Cibadak, District of Cicantayan, District of Cisaat, District of Sukaraja and District of Cirenghas. Factors that play a role in maternal mortality are patient, health personnel factors, health facility factors, and referral obstacle factors, and there are recording and reporting factors related to maternal mortality. Efforts to reduce maternal mortality are done through strengthening community empowerment systems and good services. Conclusions maternal mortality is a difficult thing to solve with complexity because it requires efforts that involve various parties.Analisis penyebab kematian maternal di kabupaten SukabumiABSTRAKKasus kematian maternal di Kabupaten Sukabumi tahun 2015 tercatatat 54 kasus kematian maternal. Pemerintah telah melakuan berbagai upaya untuk menurunkan kasus kematian maternal, tetapi hasilnya belum optimal. Identifikasi penyebab kematian maternal yang tepat, memberikan masukan berharga dalam upaya pencegahan kematian dimasa datang. Tujuan penelitian ini adalah menganalisis faktor yang berperan dalam kematian maternal dan menggali bagaimana faktor tersebut menyebabkan kematian maternal. Desaign penelitian menggunakan squensial ekplanatori disagn mixed methode yang dilakukan secara bertahap. Tahap pertama melakukan studi dokumentasi terhadap 54 kasus kematian maternal pada Otopsi Verbal Maternal dan dilakukan perhitungan statistik dengan pendekatan secara cross sectional. Hasil studi dokumen kemudian dilakukan kualitatif dengan metode wawancara mendalam. Hasil penelitian menunjukkan bahwa terdapat pengelompokan kematian maternal di kabupaten sukabumi yaitu di Kecamatan cibadak, Kecamatan cicantayan, Kecamatan cisaat, Kecamatan sukaraja dan Kecamatan cirenghas. Faktor yang berperan dalam kematian maternal ini adalah faktor pasien, faktor tenaga kesehatan, faktor fasilitas kesehatan dan faktor hambatan rujukan serta adany faktor pencatatan dan pelaporan terkait kematian maternal. Upaya penurunan kematian maternal dilakukan melalui penguatan sistem pemberdayaan masyarakat dan pelayanan yang baik.Kesimpulan faktor kematian ibu merupakan hal yang sulit untuk diselesaikan dengan kompleksitas karena memerlukan upaya yang melibatkan berbagai pihak.